CNC programming system for complex components based on KBE within integrated environment of CAD/CAPP/CAM - ZHANG, Shengwen; WANG, Guicheng; ZHANG, Liang; FANG, Xifeng (Frontiers of Mechanical Engineering, 2009)
To promote the research and development of modern digital and intelligent manufacturing technology and overcome shortcomings of computerized numerical control(CNC) programming for complex components, an innovative idea has been proposed to introduce knowledge based engineering (KBE) into the field of CNC programming within the integrated environment of CAD/CAPP/CAM. This paper constructs the architecture of CNC programming based on KBE within CAD/CAPP/CAM and explores the key technology of applying KBE to CNC programming - knowledge representation, knowledge acquisition, knowledge reasoning, and generalized knowledge base system of CNC programming. The integration of the CAD/CAM system and the CAPP system of enterprises has been achieved by taking the powerful CAD/CAM system of UG NX as a platform. The prototype system of CNC programming for complex components based on KBE within CAD/CAPP/CAM has been developed by means of UG/Open,VC++6.0, and SQL Sever 2000. Finally, a frame example, one of the complex components of a marine diesel, is presented, and the academic production and the intelligence of the system are verified.